Performance Analysis Of Yoshua Hospital From The Perspective Growth And Learning Balanced Scorecard In 2022 - Nico Aurelius Tarigan; Mardiati Nadjib Septiana (Sean Institute, 2023)
This study aims to measure the performance of Yoshua Lubuk Pakam General Hospital from a growth and learning perspective using the Balanced Scorecard. This type of research is descriptive quantitative. The data collected are secondary data and primary data. Secondary data was obtained from documentation of financial reports and human resource reports for 2022. Primary data was obtained by distributing questionnaires to hospital employees working in 2022. The results showed that hospital performance from a growth and learning perspective was generally good. Management need to pay special attention to measuring indicators that are not good or good enough, and maintain an assessment of good indicators in order to improve hospital performance in the future.